DESAIN DAN ANALISIS KEKUATAN RANGKA TEMPAT SAMPAH DI BALAI LAPAN GARUT MENGGUNAKAN METODE ELEMEN HINGGA - Lasinta Ari Nendra Wibawa (Universitas Tridinanti Palembang, 2018)
This study examined the design and analysis of the strength of the trash bin frame using the finite element method. The analysis was carried out using Autodesk Inventor Professional 2017. The frame material used was Aluminum 5052 with ISO 10799-2 (Square) standard with the size of 25 x 25 x 2 mm. Variable load of trash bin was 55 kg, 60 kg, 65 kg, and 70 kg. The simulation results show that a load of a trash bin with the weight of 55 kg, 60 kg, 65 kg, and 70 kg had the safety factor of 2,49, 2,28, 2,11, and 1,96. Keywords: aluminum 5052, finite element analysis, strength analysis, autodesk inventor 2017, trash bin frame